Cultivation and Implementation of Community-Engaged Pharmacy Services in a Free Clinic to Enhance Care for the Medically Underserved - Emmeline Tran, Pharm.D. Candidate; Brandon T. Jennings, Pharm.D (University of Minnesota Libraries Publishing, 2013)
Partnerships between community free clinics and academic medical centers improve patient outcomes and enhance learning opportunities for students. A community-academic partnership between the Maliheh Free Clinic and the University of Utah College of Pharmacy was formed to fulfill a community need for pharmacy services, to promote interdisciplinary patient care, and to provide an experiential opportunity for students. The Maliheh Free Clinic based in Salt Lake City, Utah provides free primary health care to uninsured individuals who live 150% below federal poverty guidelines. Three pharmacy services were developed and implemented. These include: 1) clinic chart reviews which involve written recommendations following a comprehensive assessment of the patient's chart examining his or her disease states and the appropriateness of his or her medications; 2) medication reconciliations and discussion of pharmacy-related recommendations with patients during Diabetes Day, an inclusive interdisciplinary patient appointment that addresses important aspects of diabetes care; and 3) an insulin dose adjustment service through a collaborative practice agreement with the clinic to monitor a patient's blood glucose levels and adjust his or her medications accordingly on a weekly basis.